Challenges and Policies for Female Sex Workers’ Readiness to Participate in Pre-Exposure Prophylaxis Program: An Explorative Qualitative Study - Sitorus, Rico Januar; Rahmiwati, Anita; Sartika, Diana Dewi; Sunarsih, Elvi; Maharani, Asri (Kesmas, 2025)
The prevalence of human immunodeficiency virus is high among female sex workers (FSWs) in Indonesia, underscoring the need for integrated prevention strategies supported by strong government policies. This study aimed to investigate FSWs' willingness to participate in a pre-exposure prophylaxis (PrEP) program. This qualitative study employed semi-structured interviews with 20 participants residing in Pangkal Pinang City, Indonesia (4 stakeholders and 16 FSWs), recruited through purposive sampling. Data were collected from July to September 2024. This non-probability sampling method was adopted due to the focus on specific study objectives and a targeted population. The analysis of the interviews revealed three theme clusters comprising eight themes. The identified clusters were government policy, knowledge of effectiveness and willingness to follow PrEP, and readiness for side effects and long-term compliance. Improving health services in areas where FSWs are concentrated is crucial for facilitating easier access with lower transportation costs. Furthermore, supporting the privacy of FSWs is crucial, and the cost of health screening before PrEP initiation should be waived to eliminate financial barriers and encourage participation in the PrEP program.